Case definition for clinical and subclinical bacterial kidney disease (BKD) in Atlantic Salmon (Salmo salar L.) in New Brunswick, Canada - Boerlage, A S (Journal of fish diseases, 2017)
© 2016 John Wiley & Sons Ltd.